Effect of series explosion effects on the fiber length, fiber dispersion and structure properties in glass fiber reinforced polyamide 66. (30th September 2020) - Guo, Kang; Wang, Dazhong; Zhang, Guizhen; Song, Jian; Wu, Ting; Qu, Jinping
Abstract : Nowadays, glass fiber (GF) reinforced polyamide 66 (PA66) composites have attracted strong interests in commercial and engineering applications due to many advantages, such as corrosion resistance, high potential of integration, self‐lubricating, and high toughness. However, it is very difficult for traditional plastic molding equipment to concurrently obtain the increase of fiber retention length and the improvement of fiber dispersion during the PA66/GF composites manufacturing, which greatly limit the widespread application of such composites. An innovative twin eccentric rotor volume pulsating plasticizing transportation equipment (TERE) based on series explosion effects, is applied to prepare PA66/GF composites at different rotor speeds and fiber loadings. Inside the PA66/GF30 composite prepared by TERE, the fibers are evenly dispersed in polymer matrix and the average fiber length increases by 3.2 times when compared to that of twin‐screw plasticizing transportation equipment (TSE). The Charpy impact strength of PA66/GF composites prepared by TERE is nearly twice that of TSE at all fiber contents. The fatigue properties, thermal oxygen aging properties, and creep properties of the TERE composites exhibit better effects than the TSE composites, indicating that the TERE can ensure longer fiber length and better dispersion effect simultaneously.